ROS-Induced Oxidative Damage and Mitochondrial Dysfunction Mediated by Inhibition of SIRT3 in Cultured Cochlear Cells - Lingjun Zhang; Zhengde Du; Lu He; Wenqi Liang; Ke Liu; Shusheng Gong (Neural Plasticity)
Sensorineural hearing loss (SNHL) is one of the most common causes of disability worldwide. Previous evidence suggests that reactive oxygen species (ROS) may play an important role in the occurrence and development of SNHL, while its mechanism remains unclear. We cultured dissected organs of Corti in medium containing different concentrations (0, 0.25, 0.5, 0.75, 1, and 1.25 mM) of hydrogen peroxide (H2O2) and established a four-concentration model of 0, 0.5, 0.75, and 1 mM to study different degrees of damage. We examined ROS-induced mitochondrial damage and the role of sirtuin 3 (SIRT3). Our results revealed that the number of ribbon synapses and hair cells appeared significantly concentration-dependent decrease with exposure to H2O2. Outer hair cells (OHCs) and inner hair cells (IHCs) began to be lost, and activation of apoptosis of hair cells (HCs) was observed at 0.75 mM and 1 mM H2O2, respectively. In contrast with the control group, the accumulation of ROS was significantly higher, and the mitochondrial membrane potential (MMP) was lower in the H2O2-treated groups. Furthermore, the expression of SIRT3, FOXO3A, and SOD2 proteins declined, except for an initial elevation of SIRT3 between 0 and 0.75 mM H2O2. Administration of the selective SIRT3 inhibitor 3-(1H-1,2,3-triazol-4-yl) pyridine resulted in increased damage to the cochlea, including loss of ribbon synapses and hair cells, apoptosis of hair cells, more production of ROS, and reduced mitochondrial membrane potential. Thoroughly, our results highlight that ROS-induced mitochondrial oxidative damage drives hair cell degeneration and apoptosis. Furthermore, SIRT3 is crucial for preserving mitochondrial function and protecting the cochlea from oxidative damage and may represent a possible therapeutic target for SNHL.